Resistance training improves hypertrophic and mitochondrial adaptation in skeletal muscle - Zhao, Y.-C.; Wu, Y.-Y. (International Journal of Sports Medicine, 2023)
Resistance training is employed for pursuing muscle strength characterized by activation of mammalian target of rapamycin (mTOR)-mediated hypertrophic signaling for protein production. Endurance training elevates peroxisome proliferator-activated receptor y coactivator 1a (PGC-1a) signaling of mitochondrial adaptations for oxidative phosphorylation. Now, emerging evidence suggests that, like endurance training, resistance training also elicits profound effects on mitochondrial adaptations in skeletal muscle, which means that resistance training yields both strength and endurance phenotypes in myofibers, which has treatment value for the muscle loss and poor aerobic capacity in humans. Our review outlines a brief overview of muscle hypertrophic signals with resistance training, and focuses on the effects of resistance training on mitochondrial biogenesis and respiration in skeletal muscle. This study provides novel insights into the therapeutic strategy of resistance training for the metabolically dysfunctional individuals with declined mitochondrial function.